2020
DOI: 10.1111/age.13019
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide assessment of diversity and differentiation between original and modern Brown cattle populations

Abstract: Identification of genomic regions involved in the phenotypic differences between original and modern Brown populations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 60 publications
3
24
1
Order By: Relevance
“…In Colombia, Creole cattle [44] reported Ho of 0.66, and the Costeño con Cuernos breed had the lowest, 0.635, and Casareño the highest, 0.733. These Ho estimates are quite different from those reported by [45], who found an average of 0.35 ± 0.167 for Ho in populations related to Braunvieh.…”
Section: Population Genetic Structurecontrasting
confidence: 99%
See 1 more Smart Citation
“…In Colombia, Creole cattle [44] reported Ho of 0.66, and the Costeño con Cuernos breed had the lowest, 0.635, and Casareño the highest, 0.733. These Ho estimates are quite different from those reported by [45], who found an average of 0.35 ± 0.167 for Ho in populations related to Braunvieh.…”
Section: Population Genetic Structurecontrasting
confidence: 99%
“…This suggests that the Mexican Braunvieh population has increased its genetic versatility for the candidate genes studied, with a higher number of heterozygous individuals. Exposure to climates different from their native climate for over a century in the tropical systems of Mexico could have caused a change in Ho, with respect to original Braunvieh populations [13,45]. On the other hand, the non-significant differences between He and Ho for most of the traits (Table 6) is similar to the results obtained in other studies, where neither the breed nor the environment modified the non-rejection of the null hypothesis, He = Ho for Xi2 [13,44,46].…”
Section: Population Genetic Structurementioning
confidence: 99%
“…The next highest RAiSD μ statistic windows in Simmental are immediately upstream of MC1R, the gene responsible for red versus black coat color in cattle (Gutiérrez-Gil et al 2007). The most significant nSL signature with a clear candidate gene resided within TMEM132D, a gene that has been identified in numerous selective sweep analyses (Qanbari et al 2014;Mészáros et al 2019;Moradian et al 2020;Moscarelli et al 2020) and is pleiotropic across dairy and beef cattle breeds (Martins et al 2020).…”
Section: Sweep Mapping Identifies Known and Novel Selected Locimentioning
confidence: 99%
“…Although less productive under intense production conditions, these local breeds may carry alleles that enabled them to adapt to local conditions. Moscarelli et al [3] reported the presence of several genomic regions that vary between original and modern Brown cattle populations, in line with their different breeding histories. Selection and genetic drift will both have contributed to the genetic differentiation between original and modern breeds.…”
Section: Introductionmentioning
confidence: 99%